تأثير الفن الإسلامي في أعمال الفنان بول كلي لوحاته أنموذجا - لوركيستي, خيرة; بوعزيز, أحلام (كلية الأدب العربي والفنون, 2024)
يهدف هذا البحث إلى أن الفن هو المحور الرئيسي من محاور اهتمامات الإنسان، والوسيلة للتعبير عن حاجاته وتحقيق ذاته، وما لبث الفن أن تطور في أدواته ومنتجاته حتى أصبح ظاهرة عامة للتعبير عن حياة الإنسان بأنماط متعددة، وتوصل البحث في هذا السياق إلى المفهوم الخاص بالفن الإسلامي، المنسوب إلى الإسلام والمرتبط بعقيدته، فهو نسق بنائي متكامل من الفنون له مصادره المعتبرة وخصائص تسع تميزه عن غيره التي جعلت منه فنا أصيلا غير مقتبس، فترك تأثيره في الفنون الغربية وقد استدعى الفن الإسلامي أنظار الفنانين الأوروبيين لطابعه الأصيل ومميزاته الجمالية من ضمنهم الفنان " بول كلي" الذي احتل مكانة كبيرة بين فناني القرن العشرين، لأسلوبه المميز وقدراته الفريدة على استخدام الخطوط والألوان في لوحاته التي تطورت بفضل الأسفار التي قام بها الفنان إلى البلدان العربية، فتمكن من إنتاج تجارب مبهرة في صور إبداعية اكتسب شهرته بفضلها This research aims to establish that art is the main axis of human interests and the means to express his needs and realize himself. Art soon developed in its tools and products until it became a general phenomenon for expressing human life in multiple styles. In this context, the research reached the concept of Islamic art. Attributed to Islam and linked to its faith, it is an integrated, constructive system of art that has its own significant sources and nine characteristics that distinguish it from others, which made it an original and not copied art. It left its influence on Western arts, and Islamic art attracted the attention of European artists due to its authentic character and aesthetic features, including the artist “Paul Klee", who occupied a great place among the artists of the twentieth century .For his distinctive style and unique ability to use lines and colors in his paintings, which developed thanks to the artist’s travels to Arab countries, he was able to produce dazzling experiments in creative images thanks to which he gained his fame.
Keywords: الفن الإسلامي،الفنون الغربية